Cancer-associated Fibroblast-derived Extracellular Vesicles Mediate Immune Escape of Bladder Cancer via PD-L1/PD-1 Expression - Feng, Rui; Li, Zhongxing; Ge, Guangcheng; Wang, Chenghao; Jia, Yuejun; Ouyang, Jun (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
Objective: Bladder cancer (BCa) is a malignant urological tumor with a high prevalence and poor prognosis. Extracellular vesicles (EVs) are increasingly becoming current hotspots owing to their involvement in cancer progression. This paper probed into the action of cancer-associated fibroblast-derived EVs (CAF-EVs) in the immune escape of BCa. Methods: CAFs were identified by immunofluorescence. EVs were extracted from CAFs via ultracentrifugation and later characterized. BCa cells (T24 cell line) were co-cultured with CD8+ T cells and then treated with CAF-EVs. The uptake of EVs by T24 cells was examined by confocal laser microscopy. T24 cell apoptosis and invasion were assessed using flow cytometry and invasion assay. CD8+ T cell proliferation was evaluated using CFSE staining. The levels of cytokines (IFN-γ, IL-2, and TNF-α) were measured by ELISA. PD-L1 and PD-1 levels were determined utilizing RT-qPCR and flow cytometry. BCa mouse models were established to identify the effect of CAF-EVs on BCa progression in vivo. Results: CAF-EVs decreased apoptosis and enhanced invasion of T24 cells, reduced proliferation of CD8+ T cells, and diminished levels of IFN-γ, IL-2, and TNF-α secreted by CD8+ T cells. CAF-EVs promoted the immune escape of T24 cells by carrying PD-L1. Downregulation of PDL1 expression in T24 cells or EVs partially counteracted the promotion of CAF-EVs on immune escape by reducing the binding of PD-L1 and PD-1. Additionally, CAF-EVs raised tumor volume and weight, upregulated PD-L1 expression, and weakened CD8+ T cell infiltration in BCa mice. Conclusion: CAF-EVs facilitate the immune escape of BCa by upregulating PD-L1/PD-1.
Keywords: immune escape